Retrospective Study of 18 Titanium Alloy Crowns Produced by Computer-Aided Design and Manufacturing in Dogs - Mestrinho, Lisa A.; Gordo, Inês; Gawor, Jerzy; Leal, Nuno; Niza, Maria (Frontiers in Veterinary Science, 2019)
Computer-aided design (CAD) and computer-aided manufacturing (CAM) technology is routinely used in various fields of human dentistry, particularly prosthodontics. Reverse engineering and additive manufacturing allow the technician to create an easier, faster and more accurate restoration, with a natural design and adequate strength. Eighteen titanium alloy full crowns were produced for canine teeth of 7 working dogs using CAD/CAM technology (3D BioCare, Nobel Biocare). Reasons for crown therapy included abrasion, enamel infraction, and crown fracture. Crown preparation was routinely performed, and impressions were delivered to the laboratory where digital impressions were performed with a lab scanner. Using 3D dental design software, the metal crown was designed and sent for manufacture. Each prosthodontic crown was then carved from a solid titanium alloy block to obtain the final crown. All prosthodontic crowns were an adequate fit, and cementation was routinely performed. Crowns were lost from 2 canine teeth during the dogs’ normal working activity, in one case, for 2 times. In all cases, replicas were requested. In the first case, the second cementation was successful. In the second case, the second crown was again lost and only the third cementation was successful. Follow up of all cases range from 12–62 months. Mean survival time for the crowns was 58.0 months. Here, CAD/CAM technology is shown to be a useful tool for manufacturing accurate prosthodontic crowns for veterinary patients. Moreover, CAD/CAM enables the production of prosthodontic crown replicas in a very short time and at relatively low cost compared to traditional methods, consequently eliminating the need for at least one anesthetic procedure in the incidence of crown cementation failure.